Associations between skating mechanical capabilities and off-ice physical abilities of highly trained teenage ice hockey players - Glaude-Roy, J.; Ducas, J.; Brunelle, J.-F.; Lemoyne, J. (European Journal of Sport Science, 2024)
This study examines the associations between force and velocity characteristics of forward skating and off-ice speed, agility, and power of highly trained teenage ice hockey players. Players attending the Quebec ice hockey federation's off-season evaluation camp were invited to participate in this study. Final sample consists of 107 highly trained teenage ice hockey players (Males: n = 38; 13.83 ± 0.38 years; Females: n = 69: 14.75 ± 0.90 years). Individual force-velocity profiles (F-V) were determined during a 44 m skating sprint. Off-ice speed, agility, and power were measured using 30 m sprint, 5-10-5 agility, and standing long jump. Associations between F-V mechanical capabilities and off-ice indicators were analyzed with correlational analyses and multivariate analysis of covariance (MANCOVA). Results of pooled data indicate that the three off-ice measures had moderate associations with F0 and V0 and large associations with Pmax. Associations with Rfmax, Drf, and Sfv were moderate to small. F0 had stronger associations with off-ice performance in female players while V0 was more important with male players. MANCOVA identified 5-10-5 times as the better predictor for F0 while 30 m sprints times better predicted V0. To maximize physical attributes of skating ability, practitioners are encouraged to focus on a general physical preparation for highly trained teenage players. Prioritizing types of exercises that use change of direction or acceleration and linear speed should have distinct effects on F0 and V0 on the ice.